Palm Oil Fresh Fruit Bunch Loss And Post Harvest Risk Analysis At Koperasi Petani Sawit Mandiri (KOPSA-M) Pangkalan Baru, Siak Hulu Kampar Riau - Angga Pramana; Anthony Hamzah; M Amrul Khoiri; Yulius Gae Lada (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2021)
Post-harvest oil palm that does not comply with the Factory standart can cause losses in reducing the production of fresh fruit bunches. The objectives of this study are 1) To analyze he stages of harvest and the sources that result in the risk of harvesting oil palm FFB in each post-harvest chain that is traversed to the TPH at the Koperasi Petani Sawit Mandiri (KOPSA-M), Pangkalan Baru Village, Kampar Regency. 2) To analyze the amount of yield loss and the possible risk of harvesting oil palm FFB in each post-harvest chain That is traversed from the land to the TPH at the Koperasi Petani Sawit Mandiri (KOPSA-M) Pangkalan Baru Village, Siak Hulu District, Kampar Regency. The data analysis was descriptive quantitative research analysis. Sources of loss post-harvest of oil palm FFB at the Pangkalan Baru Village Independent Farmers Cooperative (KOPSA-M), Siak Hulu sub-district, Kampar district is the percentage of post-harvest loss of fresh fruit bunches (FFB). is equal to 5.21 percent of the total average FFB produced per plot (2 hectares). the losses are in the land, TPH, checking raw FFB and mill sorting. The percentage of losses in the land area is 1.73 percent of the total FFB yield. Meanwhile, the number of losses in the factory sorted amount was 2.70 percent and became the most significant loss for post-harvest FFB losses at KOPSA-M. The sources of post-harvest loss of FFB at KOPSA-M are harvest time, harvesting techniques. implemented by harvesters, cleanliness of plantation land, harvesting places (TPH), fruit and plant maintainers, and sunlight, human resources (HR) from oil palm harvesters,